Gender and Media in the Broadcast Age Women's Radio Programming at the BBC, CBC, and ABC - Lloyd, Justine (Bloomsbury Academic, 2019)
The 20th century was a time of rapid expansion in media industries, as well as of accelerating demands for equality and recognition for women. While women's agency has typically been defined through the domestic sphere, the introduction of media into the home destabilised firm boundaries between public and private spheres. Gender and Media in the Broadcast Age demonstrates how women as media producers and audiences in three countries with public service broadcasters (UK, Canada and Australia) have contributed to changes in our understandings of public and private. Justine Lloyd offers a new way of understanding how tremendous changes in social definitions of gender roles played out in media forms worldwide during this period through the notion of 'intimate geographies'. Women's participation in media continues to be a key challenge to notions of the public sphere and the book concludes that profound changes initiated in the broadcast era are unfinished in the age of digital media. Lloyd therefore provides rich and valuable evidence of the dynamic relationship between media texts, producers and audiences that is relevant to contemporary debates about a growing gender 'apartheid' in a mediated culture.